1982
DOI: 10.21273/jashs.107.6.972
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mineral Nutrition and Storage on Quality Factors of ‘Jewel’ Sweet Potatoes1

Abstract: ‘Jewel’ sweet potatoes [Ipomoea batatas (L.) Lam] were grown for 2 seasons on an Orangeburg loamy sand soil with 3 N sources, 3 K rates, and 2 N rates. NH4NO3 and Ca(NO3)2 were equivalent in influence on root quality at harvest and storage, but NaNO3 significantly reduced root dry matter content. With an increase in N rate from 101 to 202 kgN/ha, weight loss during storage increased and carbohydrate levels, dry matter content, and root intercellular space values decreased. An increase in K applications from 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0

Year Published

1984
1984
2003
2003

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
2
4
0
Order By: Relevance
“…The rate of weight loss was lower during storage than during curing, consistent with previous reports (7)(8)(9)(10). The rate of storage weight loss in all cultivars was highest during the first 8 weeks of storage and lowest during the last 20 weeks.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The rate of weight loss was lower during storage than during curing, consistent with previous reports (7)(8)(9)(10). The rate of storage weight loss in all cultivars was highest during the first 8 weeks of storage and lowest during the last 20 weeks.…”
Section: Resultssupporting
confidence: 92%
“…Most previous work indicated that respiration was higher after harvest than during curing or storage (1,2,4,6,10,12); but, in one study, no decline in respiration was found over a 9-day period after harvest (15). Total weight loss rate was higher during curing than storage (7)(8)(9)(10). No information exists on the relative contribution of respiration and transpiration to total weight loss in currently grown cultivars.…”
mentioning
confidence: 89%
“…Root quality of 'Jewel' sweet potato (7) was not significantly influenced by the N sources other than a slight reduction in root dry matter content attributable to N aN 03 and when K applications were increased from 70 to 280 kg K/ha. Based on published information (7) coupled with results from this study, optimum sweet potato production and quality in the Orangeburg sandy loam soils was obtained with either NH4N 0 3 or C a(N 03)2 fertilization at 101 kg N/ha and K at 140 kg K/ha.…”
Section: Resultsmentioning
confidence: 89%
“…Numerous studies have reported effects of light levels on plants indigenous to full sun sites (2,3,5,7,12,18). Shadegrown leaves of these plants generally were thinner, had fewer epidermal and stomate cells per unit area, and fewer palisade cell layers than sun-grown leaves.…”
Section: Literature Citedmentioning
confidence: 99%
See 1 more Smart Citation